The world banking challenge : lectures and proceedings at the 25th International Banking Summer School held at Brown University, Providence, Rhode Island, August, 1972. - American Bankers Association (Washington : American Bankers Association, 1972)
The book contains the lectures delivered to the delegates of the 25th International Banking Summer School held in August, 1972 at Brown University in Providence, Rhode Island. The program, with the theme 'the World Banking Challenge" included lectures on a variety of subject important to bankers throughout the world.
osc 27/9/17
Loans
Keywords: Banks and banking; International finance; Banks and banking, International